“Fitting in whilst standing out”: Identity flexing strategies of professional British women of African, Asian, and Caribbean ethnicities - Opara, Victoria; Ryan, Michelle K.; Sealy, Ruth; Begeny, Christopher T. (Frontiers in Sociology, 2023)
Professional British women of African, Asian, and Caribbean (AAC) ethnicities contend with unique challenges and experiences in the workplace. These challenges are often due to experiences that occur at the intersection of gender and ethnic identity, thus many professional white British women (of Anglo-Saxon decent), do not face the same challenges. AAC women are more often discriminated against, excluded from informal networks, and their contributions credited to someone else. We take an intersectional theoretical approach to better understand both the disadvantaged experiences and the possible advantaged experiences that British AAC women face, based on their experiences as AAC individuals, as women and as AAC women. The study seeks to ‘give voice’ to the experiences of AAC professional women, due to the limited amount of scholarship that adequately considers their workplace experiences. We consider the ways that their identity produces qualitatively different experiences determined by the context, by the nature of interpersonal encounters or by both the context and interpersonal encounters. We conduct real-time online written interviews and utilize thematic template analysis to understand whether AAC women strategically flex identity at work. We present four major themes. These are (1) the benefits of identity flexing, (2) the role of specific stereotypes, (3) context specific opportunities, and (4) the costs of identity flexing. We draw on literature that suggests that AAC women’s identity experiences are not exclusively oppressive. We find that unique experiences, occurring at the intersection of identity facets may also yield forms of relative advantage, wherein individuals are able to adaptively leverage opportunities. Our results demonstrate that where the facets of one’s identity are more varied, there might be more chance that the particular identity will be valued in a given social context. As a result, the individual may try to assimilate with certain identity groups (through flexing), as the context directs. Nevertheless, engaging in identity flexing strategies has costs for women’s well-being, such as needing to perform increased amounts of emotional labor and heightened feelings of frustration. Overall, these costs (as well as benefits), evidence the complexities of identity flexing and the likely negative well-being implications that could ensue.